Prevalence of flat lesions in a large screening population and their role in colonoscopy quality improvement - Reinhart, K.; Bannert, C.; Dunkler, D.; Salzl, P.; Trauner, M.; Renner, F.; Knoflach, P.; Ferlitsch, A.; Weiss, W.; Ferlitsch, M. (Endoscopy, 2013)
Background and study aims: Flat lesions pose new challenges for endoscopists, but the importance of detecting them is still controversial. Most screening studies do not survey macroscopic polyp morphology. The aims were to evaluate the percentage of flat polyp findings in a large asymptomatic adult screening population (n = 52 521), to assess the impact of shape and size on malignant transformation, and to assess the role of flat lesions regarding quality assurance in colorectal cancer prevention.Material and methods: Retrospective analysis of screening colonoscopies performed between 2007 and 2011 according to the Austrian “Quality management for colon cancer prevention” program.Results: 17 771 patients with polyps were included in the study. Patients with flat polyps represented 24.2 % (n = 4293), 62.4 % (n = 11 097) were classified as having sessile and 13.4 % (n = 2381) as pedunculated polyps. Among those with flat polyps 51.4 % had adenomas (n = 2207). High grade dysplasia (HGD) was found in 2.1 % (n = 47) of flat adenomas, in 1.5 % (n = 89) of sessile adenomas and 4.7 % (n = 92) of pedunculated adenomas (P < 0.0001. The risk for containing HGD was 1.0 % for flat lesions ≤ 10 mm in size compared with 10.3 % for lesions > 10 mm, and 1.0 % for polypoid lesions ≤ 10 mm compared with 9.3 % for lesions > 10 mm (P < 0.0001). Multivariable logistic regression showed that polyp size (P < 0.0001) but not polyp shape (P = 0.438) is an independent predictor for HGD. Adenoma detection rate (ADR) correlated weakly with the flat polyp detection rate (Pearson r = 0.24).Conclusion: Malignant potential of polyps is mostly affected by size but not by shape. Since flat polyp detection rate only correlates poorly with ADR we do not recommend its incorporation in quality assured screening colonoscopy.